2009
DOI: 10.1002/anie.200900494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the [2Fe]H Subcluster Environment on the Properties of Key Intermediates in the Catalytic Cycle of [FeFe] Hydrogenases: Hints for the Rational Design of Synthetic Catalysts

Abstract: Nature's recipe: A theoretical study analyzes how the environment of the [FeFe] hydrogenase's catalytic cofactor affects its chemical properties, particularly the relative stability of complexes with bridging and terminal hydride ligands (see picture; Fe teal, S yellow, C green, N blue, O red, H gray). The results help to elucidate key rules for the design of bioinspired synthetic catalysts for H(2) production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 35 publications
9
110
0
Order By: Relevance
“…In particular, Torres et al [10] have shown that the BS approach is useful for the computation of reliable reduction potential values in Fe 4 S 4 clusters. Such results proved seminal for subsequent studies by Bruschi et al [11,12] who have used the BS approach to investigate the occurrence of protonation-coupled intramolecular electron transfers in Fe-S complexes [12]. By means of a detailed analysis of Mulliken spin populations and atomic charges, the latter authors were able to show that the active site of [FeFe]-hydrogenases-an Fe 6 S 6 cluster composed by two covalently linked Fe 2 S 2 and Fe 4 S 4 subclusters-can undergo charge transfer events of functional importance as a result of modifications in the second coordination sphere of the iron atoms.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, Torres et al [10] have shown that the BS approach is useful for the computation of reliable reduction potential values in Fe 4 S 4 clusters. Such results proved seminal for subsequent studies by Bruschi et al [11,12] who have used the BS approach to investigate the occurrence of protonation-coupled intramolecular electron transfers in Fe-S complexes [12]. By means of a detailed analysis of Mulliken spin populations and atomic charges, the latter authors were able to show that the active site of [FeFe]-hydrogenases-an Fe 6 S 6 cluster composed by two covalently linked Fe 2 S 2 and Fe 4 S 4 subclusters-can undergo charge transfer events of functional importance as a result of modifications in the second coordination sphere of the iron atoms.…”
Section: Introductionmentioning
confidence: 63%
“…This shows that, for the discussion of Mulliken charges, the choice of using a single BS spin configuration is well grounded not only in the case of small QM regions [12,21,36] but also in the case of a larger and more complex QM system including multiple Fe-S clusters. As far as Mulliken spin populations are concerned, slightly larger variations among the various BS states were observed, thus suggesting that more caution is needed for the discussion of this property in models featuring an extended BS treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the specific protein environment is believed to place constraints on the H-cluster to adopt the CO-bridged conformation and avoid the tautomerization of the terminal hydride into the more thermodynamically stable bridged hydride isomer. 11 This could well be a main reason for the impressive catalytic activities of [FeFe]-hydrogenases for hydrogen evolution with TOF up to 9000 s À1 . 12 In the [NiFe]-hydrogenases case, the protonation site could be sulfur atoms of a cysteine ligand, either bridged or terminal, and the redox platform was proposed to be centered on the Ni II center rather than on Fe II .…”
Section: Brief Overview On Structure and Function Of Natural Hydrogenmentioning
confidence: 99%
“…As a consequence, the H-cluster is constrained adopting CO-bridged conformation that exposes the vacant coordination position for terminal hydride production during the catalysis. 11 Such a phenomenon is difficult to replicate in solvated synthetic molecular [FeFe] catalysts. In order to achieve such a favorable conformation and thus enhance the activities of bio-inspired diiron catalysts, efforts are required to engineer appropriate ligand systems.…”
Section: Diiron Catalysts ([Fefe] Catalysts)mentioning
confidence: 99%
“…The surrounding protein framework finely-tunes the H-cluster and is considered to play an important role in regulating its catalytic activity, electronic properties, and potential hydride binding sites [14,23,130,[140][141][142][143]. Within the catalytic site are several conserved, charged residues that form the secondary coordination sphere, with exchangeable groups proposed to function in the transfer of protons, water coordination, and bonding interactions with the H cluster (Fig.…”
Section: Catalytic Site Structure and Coordination Spherementioning
confidence: 99%